2015
DOI: 10.1255/jnirs.1141
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Quantification of Peanut Traces in Wheat Flour by near Infrared Hyperspectral Imaging Spectroscopy Using Principal-Component Analysis

Abstract: The use of a common environment for processing different powder foods in the industry has increased the risk of finding peanut traces in powder foods. The analytical methods commonly used for detection of peanut such as enzyme-linked immunosorbent assay (ELISA) and real-time polymerase chain reaction (RT-PCR) represent high specificity and sensitivity but are destructive and time-consuming, and require highly skilled experimenters. The feasibility of NIR hyperspectral imaging (HSI) is studied for the detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 17 publications
0
28
0
1
Order By: Relevance
“…Similarly, the bulk density of wheat flour and ergot body particles in wheat flour were accurately determined and differentiated by using the HSI technique and PLSR‐based methods (Vermeulen and others ; Zhu and others ). In another study, the quantification of peanut traces in wheat flour products was conducted by applying PCA on hyperspectral images (1000 to 2200 nm) (Mishra and others ). The high R 2 P of 0.946 was obtained in quantifying peanut adulteration from 0.1% to 10% (w/w).…”
Section: Quality Evaluation Of Powdery Foodsmentioning
confidence: 99%
“…Similarly, the bulk density of wheat flour and ergot body particles in wheat flour were accurately determined and differentiated by using the HSI technique and PLSR‐based methods (Vermeulen and others ; Zhu and others ). In another study, the quantification of peanut traces in wheat flour products was conducted by applying PCA on hyperspectral images (1000 to 2200 nm) (Mishra and others ). The high R 2 P of 0.946 was obtained in quantifying peanut adulteration from 0.1% to 10% (w/w).…”
Section: Quality Evaluation Of Powdery Foodsmentioning
confidence: 99%
“…These indicated that for the two individual models, the limit of detection was 0.5%, while for the general model, the limit of detection was 1%. Mishra et al [3,32,33] studied the feasibility of the NIR HSI technique combined with principal component analysis (PCA), spectral band math, or independent component analysis (ICA) to detect peanut, hazelnut, and walnut particles (particle size of 1000-500 um) in wheat flour (particle size of 125-100 um and 212-160 um). The results of their Performance of the best PLSR models for (a) peanut-contaminated flour and (b) walnut-contaminated flour applied on prediction sets based on full spectra (an enlarged view of the green circle part was shown in the green pane).…”
Section: Selection Of Optimal Wavelengths and Multispectral Model Devmentioning
confidence: 99%
“…However, the most common methods for peanut and nut detection in food are on the basis of traditional protein detection methods, such as real-time polymerase chain reaction (RT-PCR) [1] and enzyme-linked immunosorbent assay (ELISA) [2]. Although these analytical methods are sensitive (0.1 mg/kg) [3], they are also destructive, time-consuming, require skilled operators, and even produce byproducts that are unfriendly to the environment. Thus, these laboratory-based detection techniques cannot meet the demand of the majority of food factories for online detection of nuts contamination.…”
Section: Introductionmentioning
confidence: 99%
“…In our recent earlier work (Mishra et al, 2015), the hyperspectral images were analysed using PCA to detect the peanut traces in wheat flour (down to 0.01%). The interpretation of the resulting loadings vector was not very straightforward as each PCA loadings vector represented combinations of different phenomena described by the data.…”
Section: Score Images and Images After Feature Extractionmentioning
confidence: 99%